Advanced case of PKDL due to delayed treatment: A rare case report. - Roshan Kamal Topno; Vidya Nand Rabi Das; Maneesh Kumar; Major Madhukar; Krishna Pandey; Neena Verma; Kanhaiya Agrawal; Chandra Shekhar Lal; Niyamat Ali Siddiqui; Sanjiva Bimal; Pradeep Das (Public Library of Science (PLoS), 2020)
Post-kala-azar dermal leishmaniasis (PKDL) is clinical outcome of visceral leishmaniasis (VL) and is thought to be the potential reservoir of parasite. Miltefosine (MF) is the only oral drug existing for treatment of post-kala-azar dermal leishmaniasis (PKDL). Increased miltefosine tolerance in clinical isolates of Leishmania donovani has been reported and is one of the major concerns in the treatment of PKDL. Here, we report a highly ulcerated PKDL case that was successfully cured after miltefosine treatment.